E-GUIDANCE SEBAGAI INTERPRETASI YANG INFORMATIF PADA WATERWORLD TAMAN SAFARI INDONESIA - Ronald David M (Universitas Merdeka Malang, 2016)
Development of mapping technology to explore the benefits included in the sights with digital media. Easy access through mobile maps Gadget Internet service is required. MapInfo is an application program that is used for mapping purposes. Mapping designed this author uses MapInfo is able to provide the ability to see a map of variation, improved image quality, and the editing process on each layer. Register their facilities provide more informative map display, such as determining the distance ( road and river ) or wide and the scale of a region. The use in the field of tourism provides significant benefits because it can depict a variety of attractive map display related to tourism so it is easy to interpret. DOI: https://doi.org/10.26905/jtmi.v2i1.620